Comparison of genes involved in brain development: insights into the organization and evolution of the telencephalic pallium - Jiangyan Zhang; Rui Zhao; Shiying Lin; Dong Yang; Shan Lu; Zenan Liu; Yuanyuan Gao; Yiyun Zhang; Bing Hou; Chao Xi; Jin Liu; Jie Bing; et al. (Scientific Reports, 2024)
Abstract The mechanisms underlying the organization and evolution of the telencephalic pallium are not yet clear.. To address this issue, we first performed comparative analysis of genes critical for the development of the pallium (Emx1/2 and Pax6) and subpallium (Dlx2 and Nkx1/2) among 500 vertebrate species. We found that these genes have no obvious variations in chromosomal duplication/loss, gene locus synteny or Darwinian selection. However, there is an additional fragment of approximately 20 amino acids in mammalian Emx1 and a poly-(Ala)6–7 in Emx2. Lentiviruses expressing mouse or chick Emx2 (m-Emx2 or c-Emx2 Lv) were injected into the ventricle of the chick telencephalon at embryonic Day 3 (E3), and the embryos were allowed to develop to E12–14 or to posthatchling. After transfection with m-Emx2 Lv, the cells expressing Reelin, Vimentin or GABA increased, and neurogenesis of calbindin cells changed towards the mammalian inside-out pattern in the dorsal pallium and mesopallium. In addition, a behavior test for posthatched chicks indicated that the passive avoidance ratio increased significantly. The study suggests that the acquisition of an additional fragment in mammalian Emx2 is associated with the organization and evolution of the mammalian pallium.